Digital Writing of Short Story "The Echoes of Dusun Jambu": How Creative Process Supports Cultural Literacy - Ayu, Amanda Rahma; Heriani, Dian; Simanjuntak, Tiur; Lestari, Pratiwi (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2024)
The purpose of this study is to explore how short story writing, supported by digital tools, can promote the Mengkuang River in Jambu Village as a tourist destination. It examines how the setting, cultural elements, and digital writing techniques influence the narrative, characters, and themes creatively. Using a Qualitative Research Design, the study incorporates interviews, field observations, and digital collaboration in the writing process. This research highlights the effectiveness of combining fiction, digital platforms to enhance tourism promotion and community involvement to comprehend cultural literacy, making Jambu Village's unique culture accessible to a wider audience.